Penatalaksanaan Fisioterapi Pilates dan Cat Stretch Exercise untuk Menurunkan Nyeri Haid pada Kasus Dismenore Primer - Fatimah As-syifa Khairunnisa; Adi Saputra Junaidi; Wanti Hasmar (3031-8572, 2022)
Primary dysmenorrhea is a condition of abdominal pain caused by abdominal cramps that occur during the menstrual phase and are not accompanied with patological condition of reproductive organs. Primary dysmenorrhea can be treated by pharmalogical and non-pharmalogical methods. One of the non-pharmalogical ways to treat menstrual pain is to do exercise like Pilates and Cat Stretch Exercise. This research was conducted with the aim of knowing changes in pain in cases of primary dysmenorrhea after being given physiotherapy with exercise therapy in the form of pilates and cat stretch exercises. The method used is a case study method with 1 respondent. The results of this study is Pilates and Cat Stretch Exercise can reduce menstrual pain and spasm in primary dysmenorrhea. From the 9 session of treatments, the result was a reduction in pain in patient with primary dysmenorrhea as measured by the MSQ (menstrual symptom questionnaire) form an initial value 81 to 67, this means pilates and cat stretch exercise can reduce menstrual pain in cases of primary dysmenorrhea.